Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 216 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Coquillettidia venezuelensis (Theobald, 1912)", "Country is Mexico" ] } The dataset includes 216 records from 4 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0093612-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences